Dedifferentiated Paratesticular Liposarcoma with Osseous Metaplasia - Kostas Chondros; Ioannis Heretis; Michael Papadakis; Vasiliki Bozionelou; Emmanouil Mavromanolakis; Nikolaos Chondros; Charalampos Mamoulakis (Case Reports in Urology)
Paratesticular liposarcoma is a rare tumour of the genitourinary track but the most common of all sarcomas in adults. The dedifferentiated variation occurs only in 10% of liposarcoma cases. The typical clinical presentation is similar to an inguinal hernia or a benign lipoma. We present the case of a dedifferentiated paratesticular liposarcoma with osseous metaplasia of the spermatic cord, in a male presented with acute scrotum.